GAMBARAN KUALITAS UDARA DI KOTA YOGYAKARTA BERDASARKAN PEMANTAUAN AIR QUALITY MONITORING SYSTEM TAHUN 2019-2020 - Hemida Wahyu Isramadhanti; Sigid Sudaryanto; Naris Dyah Prasetyawati; Sardjito Eko Windarso; Siti Nuryani (Unit Penelitian dan Pengabdian Masyarakat Politeknik Banjarnegara, 2022)
According to the 2019 Environmental Quality Index report, air quality in the city of Yogyakarta has decreased in the past five years. In connection with concerns about the decline in air quality in the city of Yogyakarta and its negative impact on living things, it is necessary to take steps to monitor air quality. The purpose of this study is to find out the description of air quality in Yogyakarta City in 2019 – 2020 which is reviewed through the Air Quality Monitoring System in the form of the Air Pollutant Standard Index. The type of research used is descriptive. Then the results were analyzed using descriptive analysis in the form of a comparison chart. The graph is in the form of ISPU data obtained through AQMS, an air pollutant level monitoring station. The variable in this study is ISPU data. The data collection technique was obtained by taking data from the Yogyakarta City Environmental Service website (http://iku.menlhk.go.id/aqms/) and climatological element data taken from the Meteorology, Climatology and Geophysics Agency website (www.bmkg.go. en). The results of monitoring air quality parameters have decreased and increased levels. However, based on the monitoring of the Air Quality Monitoring System in 2019-2020, the chemical parameters of air quality (PM10, SO2, CO, O3, NO2) in Yogyakarta City are still classified as